Engranando la igualdad de género en el ámbito económico-productivo - Beatriz Muriel Hernández; Daniela Romero Romay (Institute for Advanced Development Studies (INESAD), 2024)
– This working paper is a review of the conceptual framework of the economic-productive sphere and of gender equality, the aim of which is to establish theoretical-practical lines allowing progress in engaging these two spheres. In this context, equality in opportunities and in rights can be harmonized, though equality of "responsibilities, resources and retribution" by gender are more difficult to reconcile. Also, women's (economic) empowerment - seen as a way of promoting gender equality - possesses a degree of relation with the theory of growth and wellbeing when an individual has the role of consumer, for which "capabilities" are needed for selecting "functionings" that may be valued. However, when such a woman takes on the role of worker, producer or businesswoman, her seeking a high level of economic-productive performance does not imply that she is empowered, nor does the latter imply the former, though there may be a positive correlation between the two. On this basis, economic-productive interventions may harmonize with equality of opportunities by gender.
Keywords: A12; D63; I31; J16; O4; 330; economic growth; economic-productive; social well-being; gender equality; empowerment